CO-OPERATIVE BUSINESS MODEL: A SUSTAINABLE TOOL FOR PROMOTING THRIFT AND CREDIT CO-OPERATIVES FOR MICROFINANCING AMONG CO-OPERATIVE SOCIETIES IN NIGERIA. (Journal of the Management Sciences, 2023)
This paper examined the applicability of the co-operative model, focusing on thrift and credit co-operative societies, with particular reference to CEM Multipurpose Co-operative Society Limited. The objective of the study was to access the sustainability of the co-operative business to its members. Purposive sampling technique was adopted in selection of the co-operative for the study. The study was anchored on the theory of collective action. Results revealed that thrift and credit co-operatives give the members the opportunity to save and to access credit at a lower cost than the prevailing interest rate charged by the conventional banks. Members also received interest on their savings which in turn encourage savings culture of members. Members accessed credit needed for their private businesses, and also accessed credit to meet up their personal needs. A total of N17,090,500 (USD 47,474) was saved by members from January – November, 2022, where members saved varied sums of money per month, which were given out as credit (loan) to members at 6% and non-members at 10% interest rate, and the accrued interest rate shared in proportion to a member’s total contribution, at the end of the business year. Bulk contribution was also paid to the each member. The paper concluded that this practice over the years, has sustained members of thrift and credit co-operative societies in Nigeria, and enabled them to save and collect bulk money in November yearly. Since the thrift and credit co-operatives attract new members yearly, the paper recommended and encouraged non-members to join the co-operatives.
Keywords: Thrift; credit; co-operatives; Nigeria